The Relationship between Interleukin-33(IL-33) and Oxidative Stress in Diabetic Patients with Cardiomyopathy - Al-Rubaei, Zainab M. M. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Interleukin -33 (IL)-33 is among IL-1 cytokine superfamily , which shows promise as a biomarker predictive of mortality in diabetic and several cardiovascular disorders in vivo study.The objective of this study is to investigate the differences in the levels of IL-33 between healthy controls and patients with type 2 diabetes and diabetic cardiomyopathy and to investigate the correlation of IL-33 with HbA1C (biomarkers of type 2 diabetes), hs-CRP and oxidant –antioxidant status. One hundred and fifty individuals (age 40-55) were enrolled in this study which was divided into three groups as follows: G1:50 healthy control,G2: 50 subjects with type 2 diabetes mellitus,G3: 50 patients with diabetic cardiomyopathy. Fasting blood glucose (FBG) , glycated hemoglobin (HbA1C) ,high sensitive C-reactive protein(hs-CRP), malondialdehyde (MDA),uric acid ,total antioxidant capacity (TAC) and IL-33 were evaluated. The results in this study revealed highly significant increasing in FBG, HbA1C , hs-CRP ,MDA, uric acid ,and MDA/TAC ratio. while a significant decrease in TAC and IL-33 were found in patients group comparing to control group. Also a significant increase in CRP,MDA ,uric acid ,and MDA/TAC ratio were noticed for G3 compared to G2.A significant decrease in TAC and IL-33 were found for G3 compared to G2.Furthermore,a significant negative correlation between IL-33 and HbA1C, hs-CRP, and MDA/TAC ratio were found between patients groups. The conclusion could be drown from this study that the negative correlation of IL-33 levels with HbA1C ,hs-CRP and MDA/TAC levels in patients groups most possibly reflects the inflammatory component of diabetes and oxidant –antioxidant status